Pengaruh Daya Tarik Interpersonal terhadap Kohesivitas Kelompok Tani Bawang Merah di Kecamatan Mijen, Kabupaten Demak - Tri Maulana Sari; Joko Winarno; Suminah Suminah (Universitas Sebelas Maret, 2021)
Group cohesiveness as a dynamic process that is seen from the interest and attachment of relationships between members is an important thing that must be owned by farmer groups. The cohesiveness of shallot farmer groups in Mijen Sub-district, Demak Regency is influenced by several factors, one of which is interpersonal attractiveness. Cohesive groups make it easier to transfer information. The purpose of this study was to examine the level of interpersonal attractiveness of farmer group members, to examine the level of cohesiveness of farmer groups and to analyze the effect of interpersonal attractiveness on the cohesiveness of the shallot farmer group. The research method used was a saturated sample by taking all groups of shallot farmers in Mijen Sub-district, Demak Regency as samples in the study. Methods of data analysis using descriptive quantitative and simple regression analysis. The results of the study indicate that the level of interpersonal attractiveness of members of the shallot farmer group in Mijen Sub-district, Demak Regency is classified as very high or reaches 46.88%. The level of group cohesiveness is high, reaching 47.70%. Interpersonal attractiveness has a significant effect of 28% on the cohesiveness of farmer groups and the other 72% is influenced by other factors outside the study. Suggestions from the research that has been carried out are to maintain the social activities that have been carried out from the simplest things.